Recurrence characteristics after focal salvage HDR brachytherapy in prostate cancer. (March 2023) - Rasing, Marnix J.A.; Peters, Max; van Son, Marieke; Moerland, Marinus A.; Eppinga, Wietse; van de Pol, Sandrine M.G.; Noteboom, Juus; Lagendijk, Jan; van der Voort van Zyp, Jochem R.N.
Highlights: Recurrences after focal salvage HDR brachytherapy are mostly local and in-field. 3-yrs local recurrence-free survival was 51% after focal salvage HDR brachytherapy. 3-yrs local ADT-free survival was 86% after focal salvage HDR brachytherapy. Abstract: Background and purpose: Radiorecurrent prostate cancer is often confined to the prostate, predominantly near the index lesion. The purpose of this study was to look at recurrence characteristics in patients treated with focal salvage high dose-rate (HDR) brachytherapy. Materials and methods: Patients treated with MRI-guided HDR brachytherapy, with a single fraction of 19 Gy from July 2013 to October 2021 as focal salvage treatment, were prospectively included in the current study. Imaging data were collected regarding the occurrence of local, regional and distant recurrences, including location of local recurrences (LR) in relation to the HDR radiotherapy field. Results: One hundred seventy-five patients were included after focal salvage HDR brachytherapy (median follow-up 36 months (IQR 23–50)). Three-years biochemical recurrence-free survival, LR-free survival, in-field LR-free survival, out-of-field LR-free survival, any-recurrence-free survival and ADT-free survival were 43% (95%CI 34%–52%), 51% (41%–61%), 70% (61%–80%), 92% (88%–97%), 42% (32%–52%) and 86% (80%–92%), respectively. Larger GTV-size and shorter PSA doubling time were associated with in-field LR in multivariable analysis. Conclusion: After focal salvage HDR brachytherapy with a dose of 1x19 Gy for local prostate cancer recurrence, subsequent recurrences are mostly local and in-field.